PENTINGNYA PENGETAHUAN TENTANG PENYAKIT KECACINGAN DENGAN MENERAPKAN POLA HIDUP BERSIH DAN SEHAT (PHBS) - Waode Rustiah Rustiah; Sartika F. Rahman; Nurul Ni’ma Azis (Lontara Abdimas : Jurnal Pengabdian Kepada Masyarakat, 2022)
This Community Service Program aims to provide knowledge about the importance of increasing public awareness about helminthiasis by implementing a clean and healthy lifestyle (PHBS) in Kelurahan Manggala, Kecamatan Manggala, Makassar City. Worm disease is an infectious disease caused by worms that live as parasites in the human body. A person can be infected with helminthiasis when eggs or larvae enter the body, become adult worms and lay eggs in the body. A person can easily be infected by worms when living in an unsanitary environment, having poor sanitation and unhygienic habits. One of the prevention efforts is washing hands with soap after activities, especially after defecating (BAB). The risk of disease transmission can be reduced by increasing clean and healthy living behavior. The habit of washing hands should be inculcated since childhood. Children are agents of change to provide education both for themselves and their environment, as well as teach a clean and healthy lifestyle. The method of implementing this community service consists of two stages, namely: 1) Counseling and education about helminthiasis associated with the application of clean and healthy lifestyle behaviors with the lecture method; 2) Provide feedback as an evaluation to determine public understanding of the extension material presented by the speaker. The results show that this counseling provides additional knowledge about helminthiasis, as well as the enthusiasm of the community to find out how to improve sanitation in the environment and get used to maintaining personal hygiene to avoid worms. The public's understanding of the benefits of this activity is very large, as can be seen from the desire to implement a Clean and Healthy Lifestyle to avoid helminth infections.